2020
DOI: 10.1080/10447318.2020.1778351
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality Sickness: A Review of Causes and Measurements

Abstract: In virtual reality (VR), users can experience symptoms of motion sickness, which is referred to as VR sickness or cybersickness. The symptoms include but are not limited to eye fatigue, disorientation, and nausea, which can impair the VR experience of users. Though many studies have attempted to reduce the discomfort, they produced conflicting results with varying degrees of VR sickness. In particular, a visually improved VR does not necessarily result in decreased VR sickness. To understand these unexpected r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
228
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 533 publications
(325 citation statements)
references
References 100 publications
(179 reference statements)
3
228
1
5
Order By: Relevance
“…Second, VR can usually cause cybersickness. As most VR devices are developed to continuously change the field of view using 3D or 360° techniques to improve the immersive experience, motion sickness syndromes such as car sickness, sea sickness, and air sickness may occur [ 40 ]. When using the VR program, participants must be careful not to exceed one hour in a stretch and should take a 10 min break between sessions.…”
Section: Discussionmentioning
confidence: 99%
“…Second, VR can usually cause cybersickness. As most VR devices are developed to continuously change the field of view using 3D or 360° techniques to improve the immersive experience, motion sickness syndromes such as car sickness, sea sickness, and air sickness may occur [ 40 ]. When using the VR program, participants must be careful not to exceed one hour in a stretch and should take a 10 min break between sessions.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that the proliferation of Musical XR-based networked interactions partly relies on the development of computer network technologies that can address issues of bandwidth and latency [39], [80], [148]. And particularly in AV and VR systems, the sense of presence can be severely hampered by simulation sickness, a sensation theorized to be resulting from conflicting information from the vestibular and visual senses, leading to nausea, disorientation, headaches, sweating and eye strain [40].…”
Section: ) Perceptionmentioning
confidence: 99%
“…More recent research results showed that EGG is a strong indicator of nausea [ 35 , 43 , 54 ], and as such has been widely used in numerous situations related to sickness and motion sickness. A recent survey has also revealed that EGG is the third most often used objective measure (EGG, electrodermal activity, electroencephalography and eye-related measurements share the place) of virtual reality (VR) sickness [ 55 ]. Dennison et al found a statistically significant correlation of bradygastric power with disorientation and cybersickness measured with SSQ, while no correlation of SSQ measures with other physiological parameters (heart-rate, electrodermal activity, etc.)…”
Section: Introductionmentioning
confidence: 99%